Discourse on Europe's Migrant Crisis in Chinese Social Media: Recontextualising Nationalism and Defending Perceived Homogeneity. (February 2020) - Gan, Chun
Since 2015, the strong resentment in Chinese social media against international immigration triggered by the European migrant crisis has been noticed, and in many cases harshly criticised, by foreign media. Using primary sources retrieved from a major microblogging site, this article provides a critical review of the way in which the crisis was represented in popular discourse between 2015 and 2017and explores the intricate sentiments it provoked. It employs the analytical framework of critical discourse analysis developed by Fairclough to illustrate how multi-dimensional discourse construction shaped the perceptions in social media. It argues that the mostly sensationalist narratives, created through recontextualisation of long-standing nationalist discourses, reflect the dilemma between China's ambitious globalist vision for future development and the persistent myth of homogeneity of Chinese nationhood. As China undergoes a slow and reluctant transition from a traditional source of emigration to a budding destination for international immigrants, such a dilemma has broader implications for the Chinese perceptions of the European Other and China's self-positioning in the world.